2015
DOI: 10.1186/s12879-015-0809-z
|View full text |Cite
|
Sign up to set email alerts
|

How much European prescribing physicians know about invasive fungal infections management?

Abstract: BackgroundThe use of systemic antifungal agents has increased in most tertiary care centers. However, antifungal stewardship has deserved very little attention. Our objective was to assess the knowledge of European prescribing physicians as a first step of an international program of antifungal stewardship.MethodsStaff physicians and residents of 4 European countries were invited to complete a 20-point questionnaire that was based on current guidelines of invasive candidiasis and invasive aspergillosis.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 48 publications
(50 reference statements)
1
29
0
3
Order By: Relevance
“…[1][2][3][4] However, Valerio et al reported that there is a serious lack of knowledge among physicians regarding invasive fungal infection management. 5 Indeed, Apisarnthanarak et al 6 reported that inappropriate antifungal use was detected in 44%, 31% and 15% of medical departments, intensive care units (ICUs) and surgical departments, respectively. These findings suggest the importance of antifungal stewardship interventions.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
“…[1][2][3][4] However, Valerio et al reported that there is a serious lack of knowledge among physicians regarding invasive fungal infection management. 5 Indeed, Apisarnthanarak et al 6 reported that inappropriate antifungal use was detected in 44%, 31% and 15% of medical departments, intensive care units (ICUs) and surgical departments, respectively. These findings suggest the importance of antifungal stewardship interventions.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
“…Traditionally, invasive fungal diseases were thought to occur primarily in patients with haematologic cancers, transplant recipients or ICU patients, and it was believed that the physicians of these departments had enough expertise, so they did not need the help of stewardship programmes. It is now clear that, independent of the level of expertise of the group of physicians, the adherence to recommendations on antifungal drug use is extremely poor …”
Section: Appropriateness Rates For Antifungal Drugs Are Lowmentioning
confidence: 99%
“…In other words, as guided by our data, we recognise that these factors will always limit prescribing decisions and place more emphasis on solutions that can work in the face of uncertainty, inexperience and lack of knowledge. For the same reasons, our analysis draws less attention to uncertainty about technical aspects of the process of prescribing, [56][57][58][59] poor dissemination of information or conflicting guidelines and lack of awareness, 43,[60][61][62][63][64][65] and operational inefficiencies and pressures. 43,62,[66][67][68][69][70] Instead, we are looking to understand what drives the behaviour of doctors in training in the presence of these limitations -namely uncertainty, inexperience and lack of knowledge.…”
Section: Chapter 3 Findingsmentioning
confidence: 99%